Believe in the Net: the Construction of the Sacred in Utopian Tales of the Internet - Parna, Karen (Implicit Religion, 2007)
In the course of the 1990s the Internet gave rise to highly optimistic scenarios regarding its significance for humanity. In the media, in the business-guru circuit and in politics, a euphoric discourse emerged that strongly adhered to the belief that the Internet and related business methods would change the world radically and be the long-awaited vessels of earthly salvation. This paper attempts to account for such belief. It suggests that the trust invested in the extraordinary qualities of the Internet was largely based on the special meaning granted to it, which can be described as sacred. This article looks at the sources of this contemporary manifestation of the sacred and considers how the Internet became a belief with religious traits. An historical comparison between the Internet craze and the fascination with the telegraph in the nineteenth century will serve to demonstrate that there exists a longer tradition of associating new technologies with the sacred and the transcendent.